Shift Length and Shift Length Preference Among Acute Care Surgeons. Issue 3 (March 2023) - Kepros, John; Haag, Susan; Lewandowski, Karen; Bauer, Frank; Ali, Hirra; Markowski, Helen; Green, Donald; Najafi, Kaveh; Sheppard, Tina
Background: Work hour restrictions have been imposed by the Accreditation Council for Graduate Medical Education since 2003 for medical trainees. Many acute care surgeons currently work longer shifts but their preferred shift length is not known. Methods: The purpose of this study was to characterize the distribution of the current shift length among trauma and acute care surgeons and to identify the surgeons' preference for shift length. Data collection included a questionnaire with a national administration. Frequencies and percentages are reported for categorical variables and medians and means with SDs are reported for continuous variables. A chi-square test of independence was performed to examine the relation between call shift choice and trauma center level (level 1 and level II), age, and gender. Results: Data from 301 surgeons in 42 states included high-level trauma centers. Assuming the number of trauma surgeons in the United States is 4129, a sample of 301 gives the survey a 5% margin of error. The median age was 43 years (M = 46, SD = 9.44) and 33% were female. Currently, only 23.3% of acute care surgeons work a 12-hour shift, although 72% prefer the shorter shift. The preference for shorter shifts was statistically significant. There was no significant difference between call shift length preference and trauma center level, age, or gender. Conclusion: Most surgeons currently work longer than 12-hour shifts. Yet, there was a preference for 12-hour shifts indicating there is a gap between current and preferred shift length. These findings have the potential to substantially impact staffing models.